BRONCHIAL ASTHMA IN INFANTS AND PRESCHOOL CHILDREN: SPECIFICS OF BASIC THERAPY - E.A. Vishneva; R.M. Torshkhoeva; A.A. Alekseeva; Yu.G. Levina; K.E. Efendieva; A.Yu. Tomilova; N.I. Voznesenskaya (Union of pediatricians of Russia, 2011)
Due to the prevalence of allergic disease remains an urgent problem of atopy. Genetic factors play an important role in increasing the incidence, but we cannot forget about the Еnvironmental risk factors. The epigenetics explains the hereditary modifications of gene activity without changes in DNA sequence (for example, histone modifications, DNA methylation and chromatin's architectonic changes). Study of biomechanics and airway remodeling in asthma causes remain one of the most actual at present. A special category of patients with asthma - young children - requires special attention due to the anatomical, phenotypic, and emotional specifics. Selection of the basic treatment for such patients should be aimed for maximizing the effective deposition of the drug.Key words: asthma, airway remodeling, preschool children, basic therapy.